Poetics and the Question of Value; or, What Is a Philosophically Serious Poet? - WATTEN, BARRETT (Wallace Stevens Journal)
An essay is presented related to value in the context of poetics. Topics discussed include author Charles Altieri's remarks regarding poet Wallace Stevens as philosophically serious poet, poets Joshua Clover and Christopher Nealon's work on direct transposition of political economy to poetic construction, and the relation between modernism and modernity. Altieri's book "Wallace Stevens and the Demands of Modernity" is discussed.